2010
DOI: 10.1245/s10434-010-1121-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher Expression of the Heterogeneous Nuclear Ribonucleoprotein K in Melanoma

Abstract: Background-The heterogeneous nuclear ribonucleoprotein (hnRNP) K is an essential RNA and DNA binding protein involved in gene expression and signal transduction. The role of hnRNP K in cancer is relatively understudied. However, several cellular functions strongly indicate that hnRNP K is involved in tumorigenesis. Oncogenes c-Src, c-myc, and eIF4E are regulated by hnRNP K. We have shown an increased cytoplasmic hnRNP K in pancreatic cancer. In the present study, we investigated the altered expression of hnRNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
4
39
0
1
Order By: Relevance
“…These studies revealed that increased hnRNP K expression associated with poor clinical status in melanoma, prostate, breast, lung, colorectal, hepatocellular, and esophageal cancers. [14][15][16][17][18] Given the myriad of tumor types that overexpress hnRNP K in these studies and its correlation with disease prognosis, these data suggest that hnRNP K may have oncogenic functions when overexpressed.…”
Section: Clinical Evidence For a Role Of Aberrant Hnrnp K In Tumorigementioning
confidence: 75%
See 2 more Smart Citations
“…These studies revealed that increased hnRNP K expression associated with poor clinical status in melanoma, prostate, breast, lung, colorectal, hepatocellular, and esophageal cancers. [14][15][16][17][18] Given the myriad of tumor types that overexpress hnRNP K in these studies and its correlation with disease prognosis, these data suggest that hnRNP K may have oncogenic functions when overexpressed.…”
Section: Clinical Evidence For a Role Of Aberrant Hnrnp K In Tumorigementioning
confidence: 75%
“…[14][15][16][17][18] However, to directly test this notion, there is an absolute need for the development of transgenic animal models that overexpress wild-type hnRNP K. We have currently undertaken this task by generating tissuespecific Hnrnpk transgenic mice. These model systems will directly test whether hnRNP K is a bona fide oncogene and will be useful in identifying the genes and cellular programs critical for tumorigenesis when hnRNP K is overexpressed.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…hnRNPs include at least 20 discrete hnRNPs that are labeled as hnRNP A through U. These hnRNPs are actively involved in many facets of mRNA metabolism, from transcription to post-transcriptional events and translation (Papadopoulou et al, 2013;Wen et al, 2010). ELAV is another important small family of RBPs that comprises four members: HuR, HuB, HuC, and HuD.…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP K participates in the regulation of various physiological and pathological processes, including development [1822], DNA damage response [23] and several human diseases [2429]. It was reported recently that hnRNP K mRNA was gradually decreased in the rat central nervous system, but remained high in the peripheral nervous system throughout embryonic development [22].…”
Section: Introductionmentioning
confidence: 99%